Treatment of Cluster Headache by Occipital Nerve Stimulation: Case Report - Oliveira, Andressa Lima; Monteiro, Vitória Harumi Rodrigues Takahashi; Silva, Ledismar José da (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2022)
Cluster headache (CH) is a primary headache characterized by severe pain that is strictly unilateral, with orbital, supraorbital, or temporal location, accompanied by ipsilateral autonomic manifestations. It has a considerable socioeconomic impact and impairs patients' quality of life. The present study aimed to report the case of a patient presenting with CH who underwent occipital nerve stimulation and to verify the improvement in her quality of life after this procedure.
Keywords: cluster headache; treatment; neuromodulation; quality of life; nerve; anesthetic block